Deformation within the Pisco Basin sedimentary record (southern Peru): Stratabound orthogonal vein sets and their impact on fault development. (January 2016) - Rustichelli, Andrea; Di Celma, Claudio; Tondi, Emanuele; Bianucci, Giovanni
Abstract: This outcrop-based study reports diffuse joints and veins, normal to strike-slip fault zones and minor folds that developed, from Miocene to Quaternary, within the clastic to siliceous sedimentary record of the forearc Pisco Basin of southern Peru. Patterns, orientations, dimensional parameters and other outcrop-scale characteristics of the various deformation features are illustrated and their genetic mechanisms and timing of development are inferred. These new structural data and interpretations allow a better constraint of the structural style and evolution of the Pisco Basin, and can represent useful guidelines for characterizing the outcrop-scale deformation affecting similar forearc basins along the Peruvian coast. Major results of this study are that the development of the documented deformation features, their patterns, dimensional parameters and kinematics seem influenced by local perturbations of the paleostress field by mechanic processes partly independent of plate tectonics forces. These processes include strain localization on both pre-existing and progressively forming new structural discontinuities, and cyclic switches of the horizontal, principal stress axes σ2 and σ3. In particular, we discuss how different normal fault patterns, from sub-parallel to multidirectional/polygonal, could form in a same deformation phase in response of the local σ2/σ3 magnitude ratio, as an evolution of stratabound, mutually orthogonal vein sets. Highlights: Field-scale deformation features affecting the forearc, Pisco Basin strata. Structural evolution seem partly independent of plate tectonics. Normal faults as an evolution of stratabound, orthogonal vein sets. Normal fault patterns depending on the local σ2/σ3 magnitude ratio.